Comparative evaluation of three different treponemal enzyme immunoassays for syphilis - Ronnachai Viriyataveekul (2018)
Background: To reduce human errors and subjective interpretation, automation is currently a trend. However, replacing any tests with automation must first be validated. Objective: Evaluate the EIA tests performance characteristics of three commercially available enzyme immunoassays; Enzygnost Syphilis (Dade Behring Ltd), Syphilis EIA 480 (Newmarket Laboratory Ltd) and ICE* Syphilis (Abbott Murex). Material and Method: Three thousand and fifty- five serum samples were obtained from all workers who came for physical check ups before working abroad at the physical check-up unit of the out- patient department at Siriraj Hospital between February and August, 2001. Serum specimens known to be positive with VDRL and TPHA or FTA-ABS tests were included in the present study. Results: Of all the samples, 2953 were from workers who came for physical check ups; 102 were selected from known specimens positive with the Venereal Disease Research Laboratory test (VDRL) and Treponema Pallidum Hemagglutination Assay (TPHA) or Fluorescent Treponemal Antibody ABSorption (FTA-ABS) test. A true positive result was determined when the sample was reactive either with two out of three enzyme immunoassays and TPHA or FTA-ABS, or both TPHA and FTA-ABS. A true negative result was determined when the aforementioned were absent. The sensitivity and specificity of Enzygnost Syphilis, Syphilis EIA 480 and ICE* Syphilis were 100% and 97.89%, 100% and 99.59%, and 99.1% and 99.76%, respectively. The results suggest that the specificity of Enzygnost Syphilis is the lowest among these three enzyme immunoassays; the price is also the cheapest. The decision to replace an existing test depends not only on the performance characteristics but also on other factors such as cost effectiveness, turnaround time, instrument maintenance, etc. The present study shows performance characteristics, whereas an economic evaluation is only briefly mentioned regarding a hospital's decision in making test selection. Conclusion: Among the three commercial kits, the specificity of Enzygnost Syphilis was the lowest. However, the replacement of any existing test depends greatly on the purpose of the individual laboratory whereas performance characteristics will provide us with an appropriate economic evaluation.